2017
DOI: 10.1111/jace.14815
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical properties of B4C–TiB2–SiC composites toughened by composite structural toughening phases

Abstract: B 4 C-TiB 2 -SiC composites toughened by composite structural toughening phases, which are the units of (TiB 2 -SiC) composite, were fabricated through reactive hot pressing with B 4 C, TiC, and Si as raw materials. The units of (TiB 2 -SiC) composite with the size of 10-20 lm are composed of interlocking TiB 2 and SiC with the size of 1-5 lm. The addition of TiC and Si can effectively promote the sintering of B 4 C ceramics. The relative densities of all the B 4 C composites with different contents of TiB 2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…Aside from the independent second-phase particles, the interlocking MoB 2 / Mo 2 B 5 and SiC with a particle size of approximately 10-25 μm are formed in the obtained composites. The interlocking structure is similar to the units of (TiB 2 -SiC) composite structural toughening phases fabricated in previous researches of Xiaorong Zhang et al [17][18][19] Hence, we successfully fabricate the B 4 C composites with MoB 2 /Mo 2 B 5 -SiC interlocking structure via reactive hot pressing with B 4 C and MoSi 2 as raw material. The amount of the second-phase particles (MoB 2 /Mo 2 B 5 and SiC) increases with the increasing MoSi 2 content.…”
Section: Phase Composition and Microstructurementioning
confidence: 60%
See 2 more Smart Citations
“…Aside from the independent second-phase particles, the interlocking MoB 2 / Mo 2 B 5 and SiC with a particle size of approximately 10-25 μm are formed in the obtained composites. The interlocking structure is similar to the units of (TiB 2 -SiC) composite structural toughening phases fabricated in previous researches of Xiaorong Zhang et al [17][18][19] Hence, we successfully fabricate the B 4 C composites with MoB 2 /Mo 2 B 5 -SiC interlocking structure via reactive hot pressing with B 4 C and MoSi 2 as raw material. The amount of the second-phase particles (MoB 2 /Mo 2 B 5 and SiC) increases with the increasing MoSi 2 content.…”
Section: Phase Composition and Microstructurementioning
confidence: 60%
“…Metal carbides such as Cr 2 C 3 11 and metaloxides 12,13 can also enhance the sinterability of B 4 C because they can react with B 4 C to form metal borides in situ. To change the single toughening structure, Xiaorong Zhang et al 17,18 successfully fabricated B 4 C-TiB 2 -SiC composites toughened by composite structural toughening phases, where the introduced second-phase particles (TiB 2 and SiC) are interlocked, rather than disperse independently in the matrix. This effect can notably improve the mechanical properties of B 4 C ceramics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their naturally low fracture toughness and poor sinterability (sintering temperature >2000°C) limit their applications . Therefore, toughening phases, such as TiB 2 , ZrB 2 , and Al 2 O 3 are used to improve the fracture toughness of B 4 C ceramics, which generally ranges from 3 to 6.5 MPa·m 1/2 . Sintering additives, such as Al, B, C, Al 2 O 3 , or Al 2 O 3 –Y 2 O 3 , have been employed to decrease the sintering temperature and improve the SiC ceramic fracture toughness, which ranges from 2.5 to 8 MPa·m 1/2 .…”
Section: Introductionmentioning
confidence: 99%
“…Several examples of transition‐metal diboride‐silicon carbide‐boron carbide ceramics have been demonstrated. Grigoriev reported that additions of transition‐metal diborides and B 4 C improved the densification of SiC‐based compositions, with hardness values of ~26 GPa at a load of 5 N. Zhang et al demonstrated that reaction hot‐pressed B 4 C compositions reinforced with TiB 2 and SiC had hardness values up to ~36 GPa. Fahrenholtz et al reported a ZrB 2 –SiC–B 4 C ceramic with a hardness of ~43 GPa at 0.49 N.…”
Section: Introductionmentioning
confidence: 99%